A novel SVM-based average current controller for three-phase power rectification for improving the grid loads - Montazerolghaem, M.; Mesbah, M.; Islam, Syed (2011)
This paper presents a new vector-based average current controller (ACC) with constant frequency for three-phase voltage source rectifiers (VSR). The goal of this method is to utilize advantage of both ACC and SVM technique. ACC technique is widely used in DC-DC applications and four-wire converter; however the implementation of this method in three-phase ac applications has not been studied yet. ACC technique is mostly robust to the variations of the load parameters, demonstrates rapid transient performance, and is appropriate for uncomplicated implementation. The method provides the best possible current waveforms with constant switching cycle which makes it suitable for high power applications with low switching frequencies. The developed method follows the reference current value in a single switching cycle very much similar to well-known hysteresis controllers. In addition, this method benefits from constant switching frequency, also by using SVM control technique reduce switching losses. Due to important role of battery chargers for electric vehicles in smart grid systems using this method the problems associated with variable switching frequency would be minimized also a better power efficiency would be achieved. Simulation results are illustrated to show the feasibility of this method. © 2011 IEEE.